Functionalized Mesoporous Silica Membranes for CO2 Separation Applications. (6th December 2015) - Kim, Hyung-Ju; Yang, Hee-Chul; Chung, Dong-Yong; Yang, In-Hwan; Choi, Yun Jung; Moon, Jei-kwon
Abstract : Mesoporous silica molecular sieves are emerging candidates for a number of potential applications involving adsorption and molecular transport due to their large surface areas, high pore volumes, and tunable pore sizes. Recently, several research groups have investigated the potential of functionalized mesoporous silica molecular sieves as advanced materials in separation devices, such as membranes. In particular, mesoporous silica with a two- or three-dimensional pore structure is one of the most promising types of molecular sieve materials for gas separation membranes. However, several important challenges must first be addressed regarding the successful fabrication of mesoporous silica membranes. First, a novel, high throughput process for the fabrication of continuous and defect-free mesoporous silica membranes is required. Second, functionalization of mesopores on membranes is desirable in order to impart selective properties. Finally, the separation characteristics and performance of functionalized mesoporous silica membranes must be further investigated. Herein, the synthesis, characterization, and applications of mesoporous silica membranes and functionalized mesoporous silica membranes are reviewed with a focus on CO2 separation.